AB0510 Predicting Factors of Unfavorable Clinical Outcome in Lupus Nephritis. (10th June 2014) - Kishimoto, D.; Kunishita, Y.; Kamiyama, R.; Minegishi, K.; Hama, M.; Yoshimi, R.; Asami, Y.; Kirino, Y.; Ueda, A.; Takeno, M.; Ishigatsubo, Y.
Abstract : Background: There is accumulating evidence that pathological findings of the kidney are useful for predincting clinical outcomes, as Class IV in ISN/RPS classification of lupus nephritis (LN) is associated with progressive renal impairment. Tubulointerstitial inflammation (TI) is also implicated in deterioration of renal function. Objectives: To determine pre-therapeutic features including pathological and laboratory findings which are associated with unfavorable clinical outcomes of LN. Methods: We retrospectively analyzed date in 51 SLE patients (34.2 y.o. 48 female) who received renal biopsy between 2004 and 2013 in our department. The pathological findings were assessed by existence of crescent, glomerular sclerosis, TI and thrombi in addition to ISN/RPS classification. Pre-therapeutic laboratory data were reviewed. Therapeutic response (CR or non-CR) at 2 year were evaluated by SLICC renal activity and response index score (SLICC score). Results: At the baseline, eGFR, proteinuria and SLICC score were 82.7±35.1ml/min, 1.68±2.15g/day and 4.9±4.6, respectively. The renal biopsy samples were classified into Class I/II/III/IV/V (1/5/16/25/4) according to ISN/RPS classification. Crescent, glomerular sclerosis, TI, and thrombi were found 23.5%, 58.8%, 60.8%, and 19.6%, respectively. As induction therapy, corticosteroids were given to all patients, whereas intravenous infusion with CY was used for 81.3% patients having ClassIII and IV. CR rate was not different among Class I to V. The presence of glomerular sclerosis and low level of eGFR were significantly associated with non-CR (p<.05) at 2 years. Presence of crescent formation and thrombi were more frequently found in patients non-CR patients, whereas anti-phospholipid antibody was more common in CR patients, though the differences did not reach statistical significance. Conclusions: The present study showed that ISN/RPS classification did not affect CR rate and that association of TI with non-CR unlike previous studies. These findings were presumably due to the fact that therapies were mainly determined according to previously identified prognostic factors. Rather, our data showed that severe glomerular damages shown by reduced GFR and glomerular sclerosis were related with unfavorable clinical outcomes. References: Petri M, et al. Arthritis Rheum 2008;58(6):1784-1788 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5411